(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines the effect of stratification and fermentation on the germination of medicinal goji (Lycium barbarum L.) seeds. It was found that stratification is 11% more effective than fermentation in improving seed germination. Medicinal goji seeds do not germinate immediately, even under favorable conditions; a certain period of time or special treatment is required. Therefore, in addition to stratification and fermentation, the effect of temperature on seed germination was also studied. The optimal temperature for the germination of stratified seeds was determined to be +25°C. It was proven that maintaining the seeds at +25°C for 3–7 days increases germination rates up to 87.5%.